2016
DOI: 10.1016/j.kint.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Vadadustat, a novel oral HIF stabilizer, provides effective anemia treatment in nondialysis-dependent chronic kidney disease

Abstract: Current treatment of anemia in chronic kidney disease (CKD) with erythropoiesis-stimulating agents can lead to substantial hemoglobin oscillations above target range and high levels of circulating erythropoietin. Vadadustat (AKB-6548), a novel, titratable, oral hypoxia-inducible factor prolyl hydroxylase inhibitor induces endogenous erythropoietin synthesis and enhances iron mobilization. In this 20-week, double-blind, randomized, placebo-controlled, phase 2b study, we evaluated the efficacy and safety of once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
231
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(251 citation statements)
references
References 42 publications
(56 reference statements)
14
231
1
1
Order By: Relevance
“…The reticulocyte profile mimicked the predicted response to altitude-associated hypoxia [22]. Similar results were observed in a 20-week, phase 2b trial of vadadustat administered to patients with anemia secondary to NDD-CKD [23]. …”
Section: Discussionsupporting
confidence: 59%
“…The reticulocyte profile mimicked the predicted response to altitude-associated hypoxia [22]. Similar results were observed in a 20-week, phase 2b trial of vadadustat administered to patients with anemia secondary to NDD-CKD [23]. …”
Section: Discussionsupporting
confidence: 59%
“…Participants were randomized from an ESA to 300 mg once daily, 450 mg once daily, or 450 mg thrice weekly. Mean change in Hb level within each cohort remained stable throughout the study (e.g., baseline to week 16 ranged from −0.02 to −0.04 g/dl) [57].…”
Section: Vadadustatmentioning
confidence: 87%
“…In a subsequent phase IIb, double-blind, placebo-controlled trial, 210 NDD-CKD stage tjhree to five participants were randomized 2:1 into three cohorts to receive a titratable dose of vadadustat (initial dose 450 mg) or placebo once daily for 20 weeks [57]. The three cohorts were based on Hb level and ESA treatment status at screening: cohort 1 were ESA naïve (Hb ≤10.5 g/dl); cohort 2 were previously treated with an ESA (Hb ≤10.5 g/dl), and cohort 3 were actively treated with ESA (Hb ≥9.5 to ≤12.0 g/dl).…”
Section: Vadadustatmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Pergola et al studied the effect of vadadustat as compared to placebo in 210 non-dialysis-dependent CKD patients (stages 3-5) in a 20-week multi-centre phase 2b study (81). They showed that 55% of the candidates who received vadadustat achieved the primary end point (percentage of participants who during the last 2 weeks of the treatment achieved or maintained a mean haemoglobin level of >11 g/dl or an increase in haemoglobin level of ≥1.2 g/dl over the pre-dose average) as compared to 10% of the placebotreated candidates, and the drug raised and maintained haemoglobin in a predictable manner with no significant side effects as compared to placebo.…”
Section: Hif-ph Inhibitorsmentioning
confidence: 99%